ANALISIS PENDAPATAN PEDAGANG TANAMAN HIAS PADA DAERAH SENTRA DAN NON-SENTRA DI KECAMATAN TAWANGMANGU - Niken Ambarwati; Eny Lestari; Mei Tri Sundari (Universitas Sebelas Maret, 2017)
The purpose of this study is to analyze the income of ornamental plant traders living in the central area (Nglurah) and non-centers (Kalisoro and Ngledoksari). The main method of this research is descriptive analysis. The location of this research is intentional (purposive), by selecting Tawangmangu District as the research location. The method of determining the respondents was done accidentally (accidental sampling) to 30 traders of ornamental plants of the central area and 30 traders of ornamental plants of non-central areas. Data used in this research are primary data and secondary data. The data analysis method used is income analysis, multiple linear regression analysis, F test, and T-test. Based on earnings analysis shows the average total cost of local traders in the central region of 8,508,364.62 IDR with income of 14,330,849.82 IDR and income of 5,822,485.20 IDR. The average number of cost traders in non-central areas is 7,983,978.00 IDR with revenue of 14,590,483.33 IDR, and income of 6,606,505.33 IDR. The result of T-test shows that the income of ornamental plant traders in the central area is influenced by the experience of trading (X2), venture capital (X3), and land area (X6). While traders of ornamental plants in non-central areas are influenced by the experience of trading (X2), venture capital (X3), and labor in the family (X5).